Effects of Sasobit® content on the rheological characteristics of unaged and aged asphalt binders at high and intermediate temperatures - Ali Jamshidi; Meor Othman Hamzah; Mohamad Yusri Aman (Materials Research, 2012)
This paper describes the rheological properties of PG64, PG70, and PG76 asphalt binders blended with different Sasobit® contents. The rheological properties of the Sasobit®-modified binders were characterized after being subjected to different aging conditions using the dynamic shear rheometer (DSR) and rotational viscometer (RV) according to SuperpaveTM test protocols. The results indicated that the characterization of aging in terms of the Aging Index (AI) depends on the rheological property of the asphalt binder selected for use in evaluating aging, the amount of Sasobit®, the binder type, and the temperature range. Linear relationships between failure temperatures of unaged and short-term-aged asphalt were observed for three binder types. Design charts were developed to select the appropriate Sasobit® content as a function of temperature, taking into consideration the stiffening effects of Sasobit®, using the SuperpaveTM fatigue factor and asphalt mix construction temperatures.